1, 8‐Naphthyridine Derivatives: A Review of Multiple Biological Activities. Issue 12 (9th November 2015) - Madaan, Alka; Verma, Ritu; Kumar, Vivek; Singh, Anu T.; Jain, Swatantra K.; Jaggi, Manu
Abstract : The 1, 8‐naphthyridine group of compounds have gained special attention of researchers on account of their demonstrating a variety of interesting biological activities. A wide range of biological properties establishes them as potent scaffolds in therapeutic and medicinal research. The broad spectrum of activities primarily includes antimicrobial, antiviral, anticancer, anti‐inflammatory, and analgesic activities. 1, 8‐Naphthyridine derivatives have also exhibited potential applications in neurological disorders such as Alzheimer's disease, multiple sclerosis, and depression. In addition, these synthetic derivatives have been found to possess activities such as anti‐osteoporotic (α(v)β(3) antagonists), anti‐allergic, antimalarial, gastric antisecretory, bronchodilator, anticonvulsant, anti‐hypertensive, platelet aggregation inhibition, anti‐oxidant, EGFR inhibition, protein kinase inhibition, ionotropic agent, β‐3 antagonist, MDR modulator, adenosine receptor agonist, adrenoceptor antagonist, and pesticide activities. In spite of the widespread application of the 1, 8‐naphythyridine scaffolds, only a limited number of review articles are available till date. In this review, we attempt to compile and discuss the key data available in the literature for the multiple biological activities of 1, 8‐naphthyridine derivatives, in a chronological manner. This review compilation (with 199 references) may be helpful in understanding the diverse biological properties of 1, 8‐naphthyridines and provide insights into their mechanism of action. This may direct future research in the synthesis of new derivatives and exploring this scaffold for other possible biological activities. Abstract : The 1, 8‐naphthyridine (C8 H6 N2 ) scaffold is one of the six isomeric forms of diazanaphthalenes or pyridopyridines. Nalidixic acid (1‐ethyl‐7‐methyl‐4‐oxo‐[1, 8]‐naphthyridine‐3‐carboxylic acid) was the first of the synthetic quinolone antibiotics. This comprehensive review summarizes the diverse biological activities of the 1, 8‐naphthyridine derivatives reported so far.